Thermodynamics of the First Order Phase Transition of Quark-Gluon Plasma at RHIC - Kumar, Rakesh; Pandey, Sunil Kumar; Sawhney, G. L. (Asian Journal of Science and Applied Technology, 2016)
The quark-gluon plasma in thermodynamic equilibrium is reviewed. The phase diagram of quark hadron phase transition and the color superconducting phases of quark-gluon matter are discussed. The lattice QCD results on the order of the phase transition. We discuss some aspects of atomic Fermi gas in the unitary limit in the first order transition. We consider the equation of state and the critical temperature for pair condensation. The strongly interacting phase transition (Quark-Hadron phase transition) also discussed.